Exploring the dynamics: HRM practices and employee performance in Libyan commercial banks (Journal of Human Sciences, 2024)
The impact of human resource management on performance is examined. The study collected responses from  commercial banks employee . According to the findings, Employees are not happy with the compensation structure and the fairness of performance appraisals. There is a need for interventions to address these concerns according to the results of the survey. Specific sample size was identified as a limitation by the research. A nuanced understanding of HRM practices is important in the study. There is no significant impact of HRM practices on performance. Some of the things that the abstract suggests are future research directions, Advocacy for mixed-method approaches, Expanded sample sizes, And the inclusion of diverse perspectives.